Impact of Monetary Policy on Credit and Investment in Nigeria (1981 – 2020) - Aanuoluwapo Adebisi Olonila; Ditimi Amassoma; Bayode Olusanya Babatunde (Financial Markets, Institutions and Risks)
In auspicious macroeconomic setting, monetary policy should increase credit availability, particularly in the real sector, to spur investment; however, this is not the case in the Nigerian economy. In this study, the impact of monetary policy on bank credit and investment in Nigeria from 1981 to 2020 was investigated. The central bank of Nigeria's statistics bulletin was the source of the data used in this study. Using the data gathered, the study used Auto-Regressive Distributed Lag (ARDL). The study’s findings indicate that bank loans and investment have a long-term association with monetary policy. In addition, it was observed that while bank loans to the private sector and the liquidity ratio had short-term negative effects on investment, the cash reserve ratio, monetary policy, money supply, and inflation rate had long-term positive effects on investment. According to the study's findings, monetary policy significantly and favorably affects bank credit and investment in Nigeria. The study suggested that the CBN adjust the monetary policy rate by reducing the cash reserve ratio, which will increase liquidity and allow the banks to discharge their credit capacity with the aim of improving investment in Nigeria. Monetary authorities should view credit as a major channel for implementing monetary policies, and this urgent adjustment should be made.